Efecto antibacteriano in vitro del extracto de Tropaeolum majus en cepas de Streptococcus mutans ATCC 25175 - Chirinos Rodríguez, Jessica Marisol (2018)
The objective of this work was to determine the in vitro antibacterial effect of Tropaeolum majus extract "mastuerzo" in strains of Streptococcus mutans ATCC 25175. The extract was obtained by maceration with ethanol at 40º for one week. The susceptibility test was performed, using the disk diffusion method. Strains were seeded on plates with Mueller Hinton agar, embedded discs with concentrations of 10%, 20%, 30% and 40% of the extract. The plates were incubated at 37 ° C by anaerobiosis, the halos being measured after 24 hours; All the discs presented inhibition halos, whose size increased in relation directly proportional to the concentrations used, evidencing a greater diameter of inhibition halo at 40% of the extract of 16 mm. To determine the minimum inhibitory concentration (MIC), the macrodilution method was used in tubes using 10 concentrations, from the extract that showed the highest halo of inhibition; where the CMI of 8.75%(v/v) was obtained and the minimum bactericidal concentration (CMB) was obtained by the method of planting by surface in nutritive agar, obtaining a CMB of 17.5%(v/v). It is concluded that the hydroalcoholic extract of Tropaeolum majus has an antibacterial effect in vitro on strains of Streptococcus mutans ATCC 25175